Pra-rancangan Sistem Pengelolaan Arsip Surat Berbasis Website (Kasus: Kapanewon Mlati, Sleman, Yogyakarta) - Jeffry Andhika Putra; Sri Rahayu (Universitas Janabadra, 2022)
The purpose of this study was to design a mail archive management system at Kapanewon Mlati to archive government letter data (data of incoming letters, outgoing letters, incoming invitations, and outgoing invitations). With the design of this system, it is hoped that it can be implemented into a storage and archive management system in accordance with their respective fields into the system. The facts of this study indicate that the management of the Kapanewon Mlati archives has not been carried out optimally. This can be seen from the use of agenda books that are not accompanied by disposition sheets, archive storage systems that are still combined, controls that do not use form cards and the existence of damaged and dirty archives. The development of technology is currently becoming information as an important pillar with the operational activities of an institution to achieve goals that are beneficial to the institution. One technology that is currently very useful and is often used is the world wide web or known as the website. Even now the web has penetrated every agency, one of which is government agencies.